2001
DOI: 10.1007/s003300000707
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of regional cerebral blood flows by perfusion CT studies at low injection rates: a critical review of the underlying theoretical models

Abstract: IntroductionBrain metabolism is provided almost exclusively by glucose oxidation. The high metabolic demand of the brain, associated with its inability to store energy, requires an important and stable cerebral perfusion, in order to guarantee a normal cerebral function. Mean cerebral blood flow (CBF) values range around 50 cc per 100 g and per minute. They are, however, higher in young people and lower in the elderly. Regional cerebral blood flows (rCBF) are twice or thrice superior in the gray matter, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
1
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(180 citation statements)
references
References 27 publications
2
169
1
8
Order By: Relevance
“…Using a weighting factor of 0.0023mSv/(mGy ϫ cm) for the brain, the cerebral effective dose is 3.4mSv, which is quite similar to the dose level for a standard cerebral CT examination (2.5mSv). 44,46,47 Perfusion CT examination with data analysis according to the central volume principle 48 allows accurate quantitative assessment of both the rCBF and the rCBV 24 as well as definition of the cerebral infarct and penumbra, as described above. Our proposed method for the calculation of cerebral penumbra and infarct maps from the rCBF and rCBV maps provided by perfusion CT data analysis relies on (1) the reported rCBF threshold of ischemia and (2) preserved (penumbra) or altered (infarct) autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using a weighting factor of 0.0023mSv/(mGy ϫ cm) for the brain, the cerebral effective dose is 3.4mSv, which is quite similar to the dose level for a standard cerebral CT examination (2.5mSv). 44,46,47 Perfusion CT examination with data analysis according to the central volume principle 48 allows accurate quantitative assessment of both the rCBF and the rCBV 24 as well as definition of the cerebral infarct and penumbra, as described above. Our proposed method for the calculation of cerebral penumbra and infarct maps from the rCBF and rCBV maps provided by perfusion CT data analysis relies on (1) the reported rCBF threshold of ischemia and (2) preserved (penumbra) or altered (infarct) autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Чувствительность метода при применении в первые часы после начала инсульта составля-ет 96%, а специфичность 98% [10]. Достаточно давно и по сегодняшний день ПКТ является наи-более адаптированной к повседневной клини-ческой практике универсальной [11] методикой оценки мозговой перфузии при острых и хро-нических нарушениях мозгового кровообраще-ния, доступна в большинстве крупных клиник [12,13]. Однако основная доля выполняемых на сегодняшний день процедур перфузионных исследований головного мозга при нарушениях мозгового кровообращения происходит в России в региональных специализированных центрах помощи сосудистым больным и научно-исследо-вательских учреждениях.…”
Section: обзор литературыunclassified
“…Выявление с помо-щью ПКТ зон потенциально жизнеспособной и необратимо повреждённой ткани при фор-мировании ишемического очага должно быть основано не только на определении мозгового кровотока, но и на оценке соотношения между кровотоком, объёмом крови и длительностью прохождения крови в повреждённой области, то есть всеми регистрируемыми параметрами перфузии [11,21,22]. В современной отечественной и мировой литературе имеются достаточно ограниченные данные, касающиеся повышения или понижения перфузионных показателей у больных с ишеми-ческими поражениями головного мозга, а также широкий диапазон их нормальных значений, в зависимости от способов обработки первичных данных полученных при применении различных аппаратов и диагностических методик [13,23].…”
Section: рисунокunclassified
“…Furthermore, it has been demonstrated that the noise and characteristics of the operation of the machine, which suppresses helium evaporation, can cause extreme uneasiness. According to a report, people often experience greater anxiety than was once the case, due to the mental and psychological conflict induced by complex social structures, environment, and stress; at least 15% of the total population suffers from anxiety disorder [8]. In reality, a large number of examinees express anxiety during the MRI scanning procedure.…”
Section: Introductionmentioning
confidence: 99%